The impact of rifampin on the efficacy of implant retention and prosthesis removal in staphylococcal periprosthetic joint infection - Zhang, Canhong; Li, Juncheng; Lin, Lan; Liu, Mingzhong; Chen, Yang; Cai, Yuanqing; Huang, Jiexin; Huang, Zida; Zhang, Chaofan; Zhang, Wenming; Fang, Xinyu; Li, Wenbo (Frontiers in Cellular and Infection Microbiology, 2025)
ObjectivesThe purpose of this study was to evaluate the impact of adjunctive rifampicin therapy on the outcomes of prosthesis retention versus removal in patients with staphylococcal prosthetic joint infection (PJI) undergoing antibacterial treatment.MethodsA retrospective study was conducted on 227 patients diagnosed with Staphylococcal PJI from March 2014 to September 2023 who underwent debridement, antibiotics, and implant retention (DAIR) or explantation and revision surgery. Based on antimicrobial susceptibility testing, we used an effective baseline antibiotic regimen. We defined the combination of this regimen with rifampicin as the “rifampicin treatment group” and the regimen without rifampicin as the “non-rifampicin treatment group”.ResultsA total of 79 patients were included in the rifampin treatment group and 148 in the non-rifampin treatment group. There was no significant difference in the remission rate of PJI between the rifampin treatment group and the non-rifampin treatment group (79.75% vs 73.65%, p = 0.083). Additionally, Kaplan-Meier survival curve analysis showed no statistically significant difference between the two groups (p = 0.509). However, the incidence of drug-related adverse events was significantly higher in the rifampin treatment group compared to the non-rifampin treatment group (31.65% vs 8.78%, p < 0.001). There were no significant difference in treatment success rates between the use and non-use of rifampin in DAIR, one-stage revision, or two-stage revision, as well as in hip or knee joints. Binary logistic regression analysis identified diabetes and active smoking as independent significant risk factors for treatment failure, while rifampin was not an independent risk factor affecting the outcome.ConclusionThe study has not demonstrated that the standard antibiotic regimen combined with rifampin has a significant effect on the efficacy of retaining or removing prostheses in staphylococcal PJI, but rather increases drug-related adverse events. Standard surgical procedures, accurate pathogen diagnosis, and treatment are particularly crucial in the management of PJI.